ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DAGING SAPI DI PROVINSI LAMPUNG - Rino Hadiwijaya Puradireja; Herlina L.; Arief H. (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The purpose of this study was to determine the factors that influence the demand for meat in Lampung Province. The location was chosen positively (intentionally) in Lampung Province. The method used is descriptive analytical. This study uses secondary data collected from 2014-2019. Data obtained from the Badan Pusat Statistik and other agencies related to food. Based on the research results, it shows that the factors that influence the demand for beef in Lampung are the price of beef and the price of complementary goods such as the price of chicken eggs. Apart from price, beef consumption in Indonesia and economic growth in Lampung Province are the determining factors that affect beef demand.